A qualitative study of professional and carer perceptions of the threats to safe hospital discharge for stroke and hip fracture patients in the English National Health Service - Waring, Justin; Bishop, Simon; Marshall, Fiona (BIOMED, 2016)
Background: Hospital discharge is a vulnerable transitional stage in patient care. This qualitative study investigated the views of healthcare professionals and patients about the threats to safe hospital discharge with aim of identifying contributory and latent factors. The study was undertaken in two regional health and social care systems in the English National Health Service, each comprising three acute hospitals, community and primary care providers and municipal social care services. The study focused on the threats to safe discharge for hip fracture and stroke patients as exemplars of complex care transitions. Methods: A qualitative study involving narrative interviews with 213 representative stakeholders and professionals involved in discharge planning and care transition activities. Narratives were analysed in line with ‘systems’ thinking to identify proximal (active) and distal (latent) factors, and the relationships between them. Results: Three linked categories of commonly and consistently identified threat to safe discharge were identified:(1) ‘direct’ patient harms comprising falls, infection, sores and ulceration, medicines-related issues, and relapse; (2) proximal ‘contributing’ factors including completion of tests, assessment of patient, management of equipment and medicines, care plan, follow-up care and patient education; and distal ‘latent’ factors including discharge planning, referral processes, discharge timing, resources constraints, and organisational demands. Conclusion: From the perspective of stakeholders, the study elaborates the relationship between patient harms and systemic factors in the context of hospital discharge. It supports the importance of communication and collaboration across occupational and organisational boundaries, but also the challenges to supporting such communication with the inherent complexity of the care system.